Результаты исследований по разработке и применению алмазно-твердосплавных пластин из алмазов, обработанных физико-химическими методами - Никитин, Ю.И.; Богатырева, Г.П.; Гаргин, В.Г.; Стасюк, Л.Ф.; Полторацкий, В.Г.; Смекаленков, С.В.; Заболотный, С.Д. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Researches of polycrystal diamonds (PCD) from the diamonds processed by physico-chemical
methods are carried out. The method of cleaning of diamonds in peroxysulphate of ammonium and calcium
hypochloride is offered. The method of covering initial diamond micropowders by pyrolitic carbon
is studied. The way for compacting diamond crystals for diamond layer PCD is developed. It is
shown, that chemical processing methods of diamonds promote decrease of parametres of sintering
PCD, and also raise their wear resistance. The drill bits and diamond tool equipped PCD, allows to
expand essentially a range of application drilling technics at the factories of the coal industry.